PRODUCTION OF BIOGAS AT MESOPHILIC AND THERMOPHILIC TEMPERATURES (Biological Sciences - PJSIR, 2004)
Experiments were accomplished for the production of biogas using a slurry comprising 50% fresh buffalo dung and 50% water at ambient and elevated temperatures. After 2 weeks, observations for the release of biogas were noted. It was observed that with the increase of temperature, the rate of generation of gas was enhanced. A slurry containing 200 g fresh buffalo dung and 200 g water produced 121.5 ml gas / day at an average ambient temperature of 35°C, whereas at 45°C, 50°C, 55°C and 60°C, the average rates of gas generation were noted as 152.0, 221.5,292.0 and 354.0 ml / day. The volume of 232.5 ml of biogas in excess was produced with the temperature difference of 25°C (60°C - 35°C). The input of 42000 joules of energy for heating 400 ml of slurry produced gas of 5196.375 joules. It shows that there is a loss of 36803.625 joules of heat which makes the process, thermally, not viable. Hence, ambient temperature is recommended for the produc- tion of biogas for domestic plants.